New perspectives on liberal peacebuilding - Newman, Edward, 1970-; Paris, Roland, 1967-; Richmond, Oliver P. (United Nations University Press, 2009)
Peacebuilding in conflict-prone or post-conflict countries -- such as East Timor, Bosnia, Afghanistan and Sierra Leone -- aims to prevent the re-emergence or escalation of violent conflict and establish a durable peace. This volume explores and critiques the 'liberal' premise of contemporary peacebuilding: the promotion of democracy, market-based economic reforms and a range of other institutions associated with 'modern' states as a driving force for building peace. Whilst focusing mainly upon cases of major UN peacebuilding, it also considers the implications and record of liberal peacebuilding through a wider range of experiences. It goes beyond the narrow focus on democracy and market economics by interrogating a wider area of peacebuilding activities, including the (re)construction of state institutions.--Publisher's description.